Effect of Indigenous Probiotics Lactic Acid Bacteria on the Small Intestinal Histology Structure and the Expression of Mucins in the Ileum of Broiler Chickens - Ariyadi , B.; Harimurti, Sri (International Journal of Poultry Science, 2015)
Intestinal mucous containing mucins play an essential role as mucosal barrier to prevent invasion in the intestinal tissue of broilers. The aim of the study was to investigate the effect of supplementation of indigenous probiotics lactic acid bacteria on small intestinal histology structure and expression of mucins in the ileum of broiler chicken raised for 35 days. A total of 60 day old chick Lohmann strain broilers were randomly divided into four treatment groups, namely T0, T1, T2 and T3. The T0 group was raised with unsupplemented probiotics, while T1, T2 and T3 were orally supplemented multistrain probiotics at concentration 107, 108, 109 CFU/ml/bird/day, respectively. The results showed that supplementation of indigenous lactic acid bacteria probiotics significantly (P